Republic of Serbia : Third Review under the Policy Coordination Instrument-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses the Republic of Serbia's Third Review Under the Policy Coordination Instrument (PCI). Serbia is the second IMF member country to request a PCI and aims to maintain macroeconomic and financial stability, while advancing an ambitious reform agenda to foster rapid growth, job creation and improved living standards. All quantitative targets (QTs) for end-September 2019 were met. Most reform targets (RTs) have been implemented. The IMF Staff recommends completion of the third review under the Policy Coordination Instrument and establishment of end-September 2020 QTs. Fiscal policy is on track so far, however, it will be important to closely monitor 2019 budget implementation to ensure that the deficit stays within the program ceiling. While progress has been made in reforming the tax administration and strengthening public investment management frameworks, delayed reforms of the public wage system and public employment framework need to advance in 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet